Spindle Pole Organization in Drosophila S2 Cells by Dynein, Abnormal Spindle Protein (Asp), and KLP10A - Morales-Mulia, Sandra (The American Society for Cell Biology, 2005)
Dynein is a critical mitotic motor whose inhibition causes defects in spindle pole organization and separation, chromosome congression or segregation, and anaphase spindle elongation, but results differ in different systems. We evaluated the functions of the dynein–dynactin complex by using RNA interference (RNAi)-mediated depletion of distinct subunits in Drosophila S2 cells. We observed a striking detachment of centrosomes from spindles, an increase in spindle length, and a loss of spindle pole focus. RNAi depletion of Ncd, another minus-end motor, produced disorganized spindles consisting of multiple disconnected mini-spindles, a different phenotype consistent with distinct pathways of spindle pole organization. Two candidate dynein-dependent spindle pole organizers also were investigated. RNAi depletion of the abnormal spindle protein, Asp, which localizes to focused poles of control spindles, produced a severe loss of spindle pole focus, whereas depletion of the pole-associated microtubule depolymerase KLP10A increased spindle microtubule density. Depletion of either protein produced long spindles. After RNAi depletion of dynein–dynactin, we observed subtle but significant mislocalization of KLP10A and Asp, suggesting that dynein–dynactin, Asp, and KLP10A have complex interdependent functions in spindle pole focusing and centrosome attachment. These results extend recent findings from Xenopus extracts to Drosophila cultured cells and suggest that common pathways contribute to spindle pole organization and length determination.